Determinants of Corporate Income Tax: The Role of Profitability, Leverage, and Liquidity with Operating Costs as Moderating Variable - Sahrullah Sahrullah; Nadilatul Faizah (Generate Digital Publishing, 2026)
Objective: This study aims to examine the effects of profitability, leverage, and liquidity on corporate income tax, with operating costs as a moderating variable, among mining companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2025 period.Research Design & Methods: This study employs a quantitative approach, using secondary data from the annual financial reports of mining companies. A purposive sampling method was used to choose 10 companies, resulting in 70 firm-year observations. The data analysis involved descriptive statistics, classical assumption tests, multiple regression analysis, and Moderation Regression Analysis (MRA). Furthermore, the importance of the indirect effect was evaluated through the Sobel test at a 5% significance level.Findings: The research results indicate that profitability, assessed by ROA, significantly and positively affects corporate income tax. On the other hand, leverage (DAR) and liquidity (CR) do not show a notable direct impact on corporate income tax. Additionally, operating expenses have a substantial effect on corporate income tax and serve an important moderating function. The results of the Sobel test indicate that operating expenses significantly moderate the relationships between profitability, leverage, liquidity, and corporate income tax. Specifically, operating expenses amplify the positive effect of profitability on tax liability while significantly transmitting the effects of leverage and liquidity on corporate income tax.Implications: These findings indicate that mining companies must focus on improving profitability and operational cost efficiency to optimize financial performance and manage tax obligations effectively.Contribution & Value Added: This study expands the corporate taxation literature by integrating profitability, leverage, liquidity, and operating costs into a single framework. It also provides empirical evidence on the moderating role of operating costs in explaining corporate income tax behavior in the mining sector. This area remains relatively unexplored in emerging markets.